Crystallographic Orientation Identification in Multicrystalline Silicon Wafers Using NIR Transmission Intensity - Skenes, Kevin; Kumar, Arkadeep; Prasath, R. G. R.; Danyluk, Steven (Journal of electronic materials, 2018)
Near-infrared (NIR) polariscopy is a technique used for the non-destructive evaluation of the in-plane stresses in photovoltaic silicon wafers. Accurate evaluation of these stresses requires correct identification of the stress-optic coefficient, a material property which relates photoelastic parameters to physical stresses. The material stress-optic coefficient of silicon varies with crystallographic orientation. This variation poses a unique problem when measuring stresses in multicrystalline silicon (mc-Si) wafers. This paper concludes that the crystallographic orientation of silicon can be estimated by measuring the transmission of NIR light through the material. The transmission of NIR light through monocrystalline wafers of known orientation were compared with the transmission of NIR light through various grains in mc-Si wafers. X-ray diffraction was then used to verify the relationship by obtaining the crystallographic orientations of these assorted mc-Si grains. Variation of transmission intensity for different crystallographic orientations is further explained by using planar atomic density. The relationship between transmission intensity and planar atomic density appears to be linear.